Kesadaran Risiko Mahasiswa Calon Wirausahawan Kuliner Terhadap Risiko Menjalankan Bisnis Kuliner: Studi Kasus di STMA Trisakti - Bagus Suhendar; Antonia Junianty Laratmase (IJEEM - Indonesian Journal of Environmental Education and Management, 2025)
This research aims to assess the risk awareness of culinary entrepreneurship students regarding the risks associated with operating a culinary business. In addition, this research also aims to test the feasibility scale of the 'Culinary Risk Register (CRR) 2022.' The CRR is a list of risks containing 13 aspects of risk in the culinary business, derived from four risk categories: Financial, Operational, Strategic, and Hazard. The research employed a quantitative method and the Guttman Scale. The Guttman Scale was used to test the Reproducibility Coefficient and the Stability Coefficient of the CRR. The respondents of this study were sophomore students at Sekolah Tinggi Manajemen Asuransi Trisakti enrolled in the Entrepreneurship course during the Odd Semester of the 2024/2025 academic year. The results show that the students have a high level of risk awareness regarding the culinary business concept at the basic and intermediate levels. Meanwhile, regarding the complex level, the understanding varies somewhat, and the level of risk awareness is lower than that of the basic and intermediate levels. As a measurement tool (binary questionnaire), CRR 2022 demonstrates a high feasibility scale, with a Reproducibility Coefficient test score of 97% and a Stability Feasibility test score of 94%. This means that CRR is a valid binary questionnaire instrument that can be used to measure the level of risk awareness in the culinary business. The key connection between the findings of this study and the results of the 2022 Culinary Business Risk Survey is that novice entrepreneurs generally lack an understanding of the importance of preparing business contingency capital, unlike experienced entrepreneurs (respondents of the 2022 Survey). This indicates that awareness of the necessity of contingency capital constitutes a complex-level risk, which can only be fully understood after acquiring advanced managerial knowledge and direct field experience.